PENERAPAN WASIAT WAJIBAH TERHADAP NON MUSLIM DITINJAU DARI KOMPILASI HUKUM ISLAM (KHI) STUDI KASUS PUTUSAN MAHKAMAH AGUNG NO. 331/K/AG/2018/MA - Liana Noviyanti; Mulati Mulati (Jurnal Hukum Adigama, 2019)
Islamic law has stated that every person of different religion cannot inherit each other, both Muslims inherit for non-Muslims and from non-Muslims inherit for Muslims, but in practice, Judges at the Supreme Court level implement mandatory wills, this is required which has been decided in the Supreme Court Decision Number. 331 / K / AG / 2018 / MA. This study aims to examine how to implement the mandatory non-Muslim wills in the Supreme Court ruling Number. 331 / K / AG / 2018 / MA based on the provisions of the Compilation of Islamic Law (KHI), and what the Supreme Court Judges consider in implementing mandatory testaments against non-Muslims in the Supreme Court Decision Number. 331 / K / AG / 2018 / MA. This research is a normative legal research with the nature of qualitative research with the type of library research. Based on the studies that have been carried out, the Decision of the Supreme Court Number. 331 / K / AG / 2018 / MA does not include legal considerations in force in Indonesia concerning inheritance provisions and concerning the granting of an approved mandatory will set out in the Compilation of Islamic Law (KHI). The application of mandatory wills in the Supreme Court Decision is contrary to the provisions of Islamic Law and the provisions of the Compilation of Islamic Law (KHI). Article 209 paragraphs (1) and (2) concerning mandatory wills.